Investigation of Corruption Crimes in Capital Investment of West Sumbawa Regency Regional Public Company - Rizki Taufani; Jawade Hafidz (Jurnal Hukum Khaira Ummah, 2025)
This study aims to analyze the investigation into the corruption case involving equity participation in the West Sumbawa Regency Regional Public Company (Persda) at the West Sumbawa District Attorney's Office, as well as the obstacles and solutions. This study uses a sociological juridical approach, with descriptive analytical research specifications. The data used are primary and secondary data. Data collection methods include field studies and literature studies, and the data analysis method is qualitative. The theories used in this study are the theory of justice, the theory of legal systems, and the theory of legal certainty. Based on the research results, it can be concluded thatpThe investigation of the corruption crime of capital participation in West Sumbawa Regency Regional Public Company at the West Sumbawa District Attorney's Office has been in line with the applicable laws and regulations, namely the Criminal Procedure Code, the Corruption Law and Perja Number Perja Number Per-017/A/Ja/07/2014. Obstacles in the investigation of the corruption crime of capital participation in West Sumbawa Regency Regional Public Company at the West Sumbawa District Attorney's Office are the lengthy process of examining state losses by the PKP, limited human resources, inadequate facilities and infrastructure, especially related to the budget. The solution to overcome this is to coordinate intensively with the BPKP so that the audit report is completed immediately, request additional members from the Attorney General's Office if not fulfilled then maximize the existing members, request additional budget from the Attorney General's Office, if not fulfilled save the budget until the case is completed in court.